DNA Metabarcoding as a Marine Conservation and Management Tool: A Circumpolar Examination of Fishery Discards in the Diet of Threatened Albatrosses - McInnes, Julie C. (2018)
Material suplementar disponível em: http://journal.frontiersin.org/article/10.3389/fmars. 2017.00277/full#supplementary-material